The P300 as marker of inhibitory control – Fact or fiction?. (November 2020) - Huster, René J.; Messel, Mari S.; Thunberg, Christina; Raud, Liisa
Abstract: Inhibitory control, i.e., the ability to stop or suppress actions, thoughts, or memories, represents a prevalent and popular concept in basic and clinical neuroscience as well as psychology. At the same time, it is notoriously difficult to study as successful inhibition is characterized by the absence of a continuously quantifiable direct behavioral marker. It has been suggested that the P3 latency, and here especially its onset latency, may serve as neurophysiological marker of inhibitory control as it correlates with the stop signal reaction time (SSRT). The SSRT estimates the average stopping latency, which itself is unobservable since no overt response is elicited in successful stop trials, based on differences in the distribution of go reaction times and the delay of the stop-relative to the go-signal in stop trials. In a meta-analysis and an independent electroencephalography (EEG) experiment, we found that correlations between the P3 latency and the SSRT are indeed replicable, but also unspecific. Not only does the SSRT also correlate with the N2 latency, but both P3 and N2 latency measures show similar or even higher correlations with other behavioral parameters such as the go reaction time or stopping accuracy. The missing specificity of P3–SSRT correlations, together with the general pattern of associations, suggests that these manifest effects are driven by underlying latent processes other than inhibition, such as behavioral adaptations in context of performance monitoring operations.